A phase I study of panobinostat in children with relapsed and refractory hematologic malignancies. (17th August 2020) - Goldberg, John; Sulis, Maria Luisa; Bender, Julia; Jeha, Sima; Gardner, Rebecca; Pollard, Jessica; Aquino, Victor; Laetsch, Theodore; Winick, Naomi; Fu, Cecilia; Marcus, Leigh; Sun, Weili; et al.
Abstract: Background: Panobinostat demonstrates activity against pediatric cancers in vitro. A phase I trial in children with refractory hematologic malignancies was conducted. Study design: The trial evaluated two schedules of oral panobinostat using 3 + 3 dose escalations in 28-day cycles. For children with leukemia, panobinostat was given once daily three days a week each week at 24, 30 and 34 mg/m2/day. For children with lymphoma, panobinostat was given once daily three days a week every other week at 16, 20 and 24 mg/m2/day. Cerebrospinal fluid (CSF) from Day 29 of the first cycle, when available, was evaluated for PK. The study was registered on clinicaltrials.gov (NCT01321346) Results: Twenty-two subjects enrolled with leukemia. Five enrolled at dose level 1, 6 at dose level 2, and 11 at dose level 3. There was one dose limiting toxicity (DLT) in the leukemia arm at dose level 3 (Grade 4 hypertriglyceridemia), but no maximum tolerated dose (MTD) was identified. No subjects required removal from protocol therapy for QTc prolongation. PK studies were available in 11 subjects with similar exposure in children as in adults. Four Day 29 CSF specimens were found to have panobinostat levels below the lower limit of quantification. Five subjects with lymphoma were enrolled and received study drug, and 4 were evaluable for DLT. A DLT was reported (Grade 3 enteritis) on the lymphoma arm. Conclusions: Panobinostat was tolerated in heavily pretreated pediatric subjects. Gastrointestinal effects were observed on this study. There were no cardiac findings. There were no responses.